How to compose a narrative: Students' approaches and pedagogical implications. (9th April 2019) - Thorsten, Anja
Abstract : The purpose of this paper is to contribute knowledge on children's narrative writing from a pedagogical perspective. Through analyses of nine- to ten-year-old students' narrative writing, aspects that are critical to discern in order to write narratives with a well-developed plot are formulated. The theoretical framework is narratology theories and Variation Theory. Narratology provides a conceptual framework for describing narrative writing, while Variation Theory offers a pedagogical perspective. A total of 80 narratives written by students have been analyzed, and five qualitatively different approaches to writing were seen. Narrative writing can be approached as describing events, solving a problem, creating action, making jokes and composing a narrative. A comparison between these approaches revealed five aspects that are critical for children to discern in order to develop the ability to write narratives: the discernment of a reader, the function of a narrative, the narrative structure, coherence, and duration. These aspects can be discerned in a more or less powerful way. The study contributes to the field by offering teachers guidance in what aspects are critical to address when teaching narrative writing in school.